Impact of chitosan-based coatings on myofibrillar protein denaturation, muscle microstructure and lipid oxidation of oyster (Crassostrea hongkongensis) during 0 °C storage. Issue 10 (25th November 2020) - Chen, Xiuli; Lv, Min; Gan, Hui; Zeng, Digang; Yang, Chunling; Ma, Huawei
ABSTRACT: The changes in myofibrillar protein, muscle microstructure, and lipid oxidation of oysters ( Crassostrea hongkongensis ) treated with chitosan-based coatings (CP-0°C) or aseptic water (CG-0°C) for 20 days storage at 0°C were investigated. Compared to the CG-0°C at day 20, the higher total sulfhydryl group content (83.24%), unfrozen water content (39.24%), and Ca 2+ -ATPase activity (96.79%) along with the lower myofibrillar protein solubility (80.15%) indicated that CP-0°C protected oysters from protein denaturation. Similarly, the CP-0°C better maintained muscle microstructure shown by the relatively higher quality of muscle and less ice crystals. Meanwhile, CP-0°C prevented lipid hydrolysis and oxidation, as evidenced by the lower contents of fatty acid (FA) content (total content of 12.16 ± 1.02 mg/g wet weight at day 20), peroxide value (POV) (15.13 meq oxygen/Kg lipid at day 20), and thiobarbituric acid-reactive substances (TBARS) (1.79 mg MDA eq/Kg sample at day 20) in CP-0°C. These results imply that CP-0°C could protect the quality of chilled oysters stored at 0°C.